New bathyal Anachis (Neogastropoda: Buccinoidea: Columbellidae) from the Southwestern Atlantic, and the designation of a lectotype for A. stricta (Watson, 1882) - Lima, Silvio Felipe Barbosa; Guimarães, Carmen Regina Parisotto (Zootaxa, 2015)
Mollusks are the marine invertebrates with the greatest diversity (Bouchet et al. 2002), and account for one of the highest number of descriptions of new species (Bouchet 1997, 2006). A total of 1776 species of marine mollusks have been cataloged for Brazil (Rios 2009). Knowledge of species richness in the country has increased mainly due to the discovery of new deep sea mollusks (see Lima & Christoffersen 2013, 2014; Lima et al. 2013, 2014; Corrêa et al. 2014; Lima 2014; Simone & Cunha 2012, 2014).